Inhalation therapy for bronchial asthma in the conditions of paediatric section - W. V. Delyagin (Медицинский совет, 2020)
The prevalence of bronchial asthma among children in different regions of Russia ranges from 10.9–9.6‰ to 50–55‰. The frequency of bronchial asthma among lyceum students is 33.1‰, while in the most overcrowded school it is 45.8‰. Bronchial asthma occurs more frequently in the mild, less frequently in the medium form. Therefore, the main burden on the management of such patients falls on the ambulatory segment. Diagnosed on the basis of respiratory symptoms such as wheezing, difficulty breathing, strain and bloating of the chest, coughing. Asthmatic attack with bronchial asthma of any degree of severity can be as severe or even asthmatic status, which, along with the prevalence of bronchial asthma, determines the primary importance of ambulatory control of the disease. It is fundamental to suppress local bronchial inflammation and remove bronchospasm. Adequacy and systematic treatment is essential for the outcome of bronchial asthma in children. Timely anti-inflammatory treatment can lead to remission. Inhalation techniques of anti-inflammatory drugs and bronchodilators are the most optimal. The possibility of application of beclometasone (inhalation glucocorticosteroid), a combination of fluticasone and salmeterol, ipratropium bromide of Russian manufacture, which efficiency is proved in practical work and economically justified, is considered. IGCS, acting locally, have a pronounced anti-inflammatory activity, suppressing both acute and chronic inflammation. Clinical examples of children with atopic dermatitis and the revealed diagnosis of bronchial asthma, with an optimum choice of treatment are given. It is proved that application of modern inhalation drugs in complex treatment leads to bronchial asthma remission.